Religious interests in community conflict : beyond the culture wars - Djupe, Paul A.; Olson, Laura R., 1967- (Baylor University Press, 2007)
This volume investigates some of the most visible issues in American politics today, including gay marriage and race, along with ongoing concerns that often fly below the radar of the mass media, such as healthcare and homelessness. The book uncovers explores the political motivations, effectiveness, and interplay of organized religious interests as they confront public problems in their local communities.